Content And Educational Resources Of The Development Of Digital Competence In Students Of Pedagogical Higher Educational Institutions - Sheraliyev Odiljon Shuxratjon ugli (International Journal on Integrated Education, 2023)
This article presents the content of the development of digital competence in students of pedagogical higher education institutions, problems that will become an obstacle to the development of digital competencies, the positive impact of the digitized educational environment on students, the classification of educational resources aimed at the development of digital competencies